Kesadaran Ekologis Pasca Pandemi: Sebuah Tinjauan Filosofis: A PHILOSOPHICAL REVIEW - Rangga Mahaswa; Putu Pradnya Lingga Dharmayasa (LIPI Press, 2021)
This article explains neglected the ecological awareness during Covid-19 pandemic. The global community focused more on increasing public health awareness than reflecting and reviewing the forgotten space—the affected environment. The affected environment consists of the social and the natural environment. However, ecological awareness recognizes both. Added to that, the Anthropocene is a marker of ecological crisis and environment has become less habitable due to mass-anthropogenic activities in indirectly determining the notion of ecological awareness. Ecological awareness is essential for realizing a new normal society based on transformative movement and adaptive change. This research uses a literature review and a philosophical approach to reformulate ecological awareness in the post-pandemic world. its idealization must recognize the diversity of ecological awareness in terms of social transformation. There are several cultural strategies to build ecological awareness. First, idealization level concerning concept or world-view toward ‘what is ecological awareness?’. Second, the formulation level for post-pandemic ecological awareness formulation. Third, the real political movement oriented towards implementation. Therefore, the value of ecological awareness as a cultural strategy expects to recognize non-human existence, to avoid class discrimination and impartiality towards nature and society in the post-pandemic world.